Normal Gallbladder Ejection Fraction Occurring Unexpectedly Obviates Need for Sincalide Stimulation. (May 2017) - Hadi, Samir; Tulchinsky, Mark
Abstract : Abstract: A 25-year-old man was referred for chronic right upper quadrant abdominal pain for hepatobiliary scintigraphy to evaluate the gallbladder (GB) function. An unexpected GB contraction with ejection fraction (EF) of 90% was observed during the first hour of baseline imaging. Subsequent stimulation with sincalide produced GB EF of 99%. A similar case previously reported also showed normal unexpected GB EF that predicted similar post–sincalide GB EF. These examples support what should be evident: A normal unexpected GB EF is a sufficient evidence for a normal GB function and should obviate need for sincalide stimulation.